Identifikasi Berita HOAX Berbasis Web Menggunakan Algoritma C4.5 - Edward Edward (Fakultas Teknologi Informasi Universitas Tarumanagara, 2021)
Now we can get news from anywhere and anytime, for example, such as news sites or social media that are commonly used, there are many social media options such as Facebook, Twitter, WhatsApp, and many other. But the information that is disseminated does not really contain some news that does not match the truth or is often called HOAX. HOAX is information that is untrue or real, but it is made to appear as if it were. The author's goal in creating HOAX classification system news is to help potential users to be able to identify a news item whether the news is HOAX news or not. This system is designed based on a website using the Python programming language. The C4.5 algorithm will be used to classify or determine whether a news is HOAX news or not. The results of the C4.5 method have an excellent accuracy value with an accuracy value of 99.6%